Health-related quality of life and coping strategies adopted by COVID-19 survivors: A nationwide cross-sectional study in Bangladesh. - Mohammad Anwar Hossain; Rubayet Shafin; Md Shahoriar Ahmed; Md Shohag Rana; Lori Maria Walton; Veena Raigangar; Tasnim Ara; Md Aminul Hoque Rasel; Mohammad Sohrab Hossain; Md Feroz Kabir; Mir Raihanul Islam; Md Nazmul Hasan; et al. (PLoS ONE, 2022)
Introduction This study aims to investigate the health-related quality of life and coping strategies among COVID-19 survivors in Bangladesh. Methods This is a cross-sectional study of 2198 adult, COVID-19 survivors living in Bangladesh. Data were collected from previously diagnosed COVID-19 participants (confirmed by an RT-PCR test) via door-to-door interviews in the eight different divisions in Bangladesh. For data collection, Bengali-translated Brief COPE inventory and WHO Brief Quality of Life (WHO-QoLBREF) questionnaires were used. The data collection period was from October 2020 to March 2021. Results Males 72.38% (1591) were more affected by COVID-19 than females 27.62% (607). Age showed significant correlations (p<0.005) with physical, psychological and social relationships, whereas gender showed only a significant correlation with physical health (p<0.001). Marital status, occupation, living area, and co-morbidities showed significant co-relation with all four domains of QoL (p<0.001). Education and affected family members showed significant correlation with physical and social relationship (p<0.001). However, smoking habit showed a significant correlation with both social relationship and environment (p<0.001). Age and marital status showed a significant correlation with avoidant coping strategies (p<0.001); whereas gender and co-morbidities showed a significant correlation with problem-focused coping strategies (p<0.001). Educational qualification, occupation and living area showed significant correlation with all three coping strategies(p<0.001). Conclusion Survivors of COVID-19 showed mixed types of coping strategies; however, the predominant coping strategy was avoidant coping, followed by problem-focused coping, with emotion-focused coping reported as the least prevalent. Marital status, occupation, living area and co-morbidities showed a greater effect on QoL in all participants. This study represents the real scenario of nationwide health-associated quality of life and coping strategies during and beyond the Delta pandemic.